Bi2MoO6 / VC / C-C composite photoelectric catalyst as well as preparation method and application thereof
By recombining Bi2MoO6 with VC and depositing on a C-C substrate, the problems of low light absorption rate and slow reaction kinetics of electrode materials in the photoelectrochemical water decomposition system are solved, and efficient and stable solar to hydrogen energy conversion efficiency is achieved.
Patent Information
- Application Number
- CN202411749682.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-02
AI Technical Summary
In the existing photoelectrochemical water decomposition system, the electrode material has low light absorption, severe charge recombination and slow reaction kinetics, making it difficult to achieve efficient and stable solar energy to hydrogen energy conversion efficiency.
Bi2MoO6/VC/C-C composite photoelectric catalyst is used, which forms a nanosheet-like structure and heterojunction by recombining Bi2MoO6 with VC and depositing it on a C-C substrate, thereby enhancing light absorption and electron transfer efficiency.
The oxygen evolution efficiency of the photoelectric catalyst is improved, the conductivity, adsorption energy and reaction kinetics are improved, and the efficiency of photoelectrochemical water decomposition is effectively improved.
Smart Images

Figure CN119549172A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of functional materials and relates to photoelectrocatalytic materials, and specifically to a Bi2MoO6 / VC / CC composite photoelectrocatalyst and a preparation method and application thereof. Background Art
[0002] Energy issues are one of the biggest challenges facing human society today. Developing a clean and sustainable new energy source is an effective strategy to solve this problem. At present, the full development and utilization of solar energy is gradually becoming a research trend in energy utilization. Photoelectrochemical (PEC) water splitting to produce hydrogen by converting solar energy into hydrogen (H2) is a very promising strategy for solar energy utilization. This method converts solar energy into equally clean and sustainable hydrogen energy for storage and utilization. A complete PEC system includes a photocathode, a photoanode and an electrolyte. To obtain an efficient PEC water splitting system, it is necessary to develop stable, efficient and inexpensive electrode materials to achieve efficient conversion efficiency of solar energy to hydrogen energy. During the operation of the PEC water splitting system, the light absorption efficiency, charge transfer efficiency and interface transfer efficiency of the charge jointly determine the performance of the device. The electrode materials currently studied still face the problems of low light absorption, severe charge recombination and slow reaction kinetics. In order to solve these problems, it is necessary to develop excellent semiconductor materials and further optimize the materials through strategies such as morphology regulation, doping and heterojunction construction, so as to achieve efficient and stable photoelectrochemical water splitting to produce hydrogen and oxygen.
[0003] Bismuth molybdate (Bi2MoO6) is made from MoO4 2- With Bi2O2 2+ Layered Aurivillius compounds formed by alternating stacking. The built-in electric field is composed of MoO4 2- With Bi2O2 2+The heterogeneous charge polarization between the two species is beneficial to improve the separation efficiency of photogenerated carriers. Bi2MoO6 shows great potential in the field of visible-light-driven photocatalysis due to its narrow band gap, high stability and environmental friendliness. However, bismuth-based catalysts also have some disadvantages, such as small specific surface area, long migration distance of photogenerated carriers and high possibility of bulk recombination. In order to further enhance the performance of PEC of Bi2MoO6, considerable efforts have been made on various chemical modifications (such as doping) and heterostructures. However, nanoengineering provides us with a completely different approach to improve PEC performance by adjusting intrinsic electrochemical processes such as surface reactions and charge separation / migration. Transition metal carbides (TMCs) are members of many catalysts composed of non-precious transition metals, and they have been known for their "Pt-like behavior" since 1973. Mo2C and W2C are typical representatives of TMCs and have been widely studied as efficient and promising HER electrocatalysts. Compared with the former, VB group metal carbides, especially vanadium carbide (VC), have attracted extensive attention due to their high natural abundance, low cost and low density. However, the electrocatalytic activity of VC is still unsatisfactory due to the inappropriate interaction between the surface and the reaction intermediates. Therefore, it is necessary to tune its catalytic performance through surface modification and defect engineering. Summary of the invention
[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a Bi2MoO6 / VC / CC composite photoelectric catalyst and its preparation method and application. The photoelectric catalyst is a composite photoelectric catalytic material composed of Bi2MoO6 and VC deposited on a CC substrate after being compounded, wherein the heterogeneous structure formed after the thin nanosheet structure of Bi2MoO6 and VC are compounded increases the range of light absorption and enhances the transfer of electrons, and the surface of the CC substrate is loose and porous. After compounding, the oxygen evolution efficiency of the Bi2MoO6 / VC / CC composite photoelectric catalyst is effectively improved.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A method for preparing a Bi2MoO6 / VC / CC composite photoelectric catalyst comprises the following steps:
[0007] Step 1: Sodium molybdate dihydrate and bismuth nitrate pentahydrate powders are prepared in a mass ratio of 1: (1-3), mixed evenly, placed in a white magnetic boat, placed in a tube furnace, and heated from room temperature to 500-700°C at a rate of 5-20°C / min under the protection of an inert atmosphere of Ar, and kept warm for 2-4 hours. After the product is cooled, it is taken out, ground, centrifuged, washed and dried to obtain a Bi2MoO6 precursor;
[0008] Step 2: ammonium metavanadate, dicyandiamide and urea are mixed in a mass ratio of 1:(0.5-4):(1-5), placed in a white magnetic boat, put into a tube furnace, and heated from room temperature to 800-1000°C at a rate of 5-20°C / min under the protection of an inert atmosphere of Ar, and kept warm for 2-4 hours. After the product is cooled, it is taken out and ground to obtain VC powder;
[0009] Step 3: Take 0.3-0.6 g of Bi2MoO6 powder prepared in step 1 and VC powder prepared in step 2 and place them in the same beaker, add 30-50 mL of deionized water, stir until uniformly dispersed, then add 0.005-0.02 g of polyvinyl alcohol, continue stirring until uniformly dispersed, obtain a precursor solution and transfer it to a crucible;
[0010] Step 4: Set the working temperature of the muffle furnace to 140-180°C. When the temperature inside the muffle furnace rises to the set temperature, place the crucible containing the precursor solution in the muffle furnace and keep it warm for 5-15 minutes. Then, take it out with crucible tongs, immerse the cleaned CC substrate in the solution for 1-10 minutes, take out the CC substrate, and obtain the desired Bi2MoO6 / VC / CC photoelectric catalyst after drying.
[0011] The present invention also has the following technical features:
[0012] Preferably, the grinding in step 1 and step 2 is performed using a mortar for 40 to 120 minutes.
[0013] Preferably, the centrifugal washing in step 1 is to transfer the product to a centrifuge tube, separate the solid after centrifugation at 8000-12000 r / min for 5-15 min, and rinse with deionized water and anhydrous ethanol alternately for 3-5 times.
[0014] Preferably, the drying in step 1 and step 4 is to place the product in a vacuum drying oven at 80° C. and dry it for 8 to 16 hours.
[0015] Preferably, the stirring time in step 3 is 5 to 10 min, and the stirring rate is 500 to 700 r / min.
[0016] Preferably, the CC substrate in step 4 is cleaned by placing the substrate in a beaker and performing alternating ultrasonic cleaning with water and alcohol for 20 minutes.
[0017] The present invention also protects a Bi2MoO6 / VC / CC composite photoelectric catalyst prepared by the method as described above and its application as a photoanode in photocatalytic electrolysis of water.
[0018] Compared with the prior art, the present invention has the following technical effects:
[0019] In the process of preparing Bi2MoO6 / VC / CC photoelectrocatalytic materials, the present invention combines the solid phase sintering method with the hot impregnation method. The required raw materials are first mixed and synthesized by simple solid phase sintering, and then the composite photoelectrocatalytic material is obtained by one-step impregnation. The entire preparation process is simple, the conditions are easy to control, the production cost is low, and it is easy to industrialize production. The prepared product has high purity and good crystallinity.
[0020] The Bi2MoO6 / VC / CC photoelectric catalyst prepared by the present invention is a composite photoelectric catalytic material composed of Bi2MoO6 and VC deposited on a CC substrate, wherein the thin nanosheet structure of Bi2MoO6 is compounded with VC to construct a heterojunction with strong electronic interaction at the two-phase heterogeneous interface, which increases the range of light absorption, enhances electron transfer, and can improve the overall conductivity, adsorption energy and reaction kinetics. The surface of the CC substrate is loose and porous, and can present more active sites to effectively promote the separation and transmission of photogenerated charges. After compounding, the oxygen evolution efficiency of the Bi2MoO6 / VC / CC composite photoelectric catalyst is effectively improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is the X-ray diffraction analysis diagram of Bi2MoO6 prepared in Example 2;
[0022] Figure 2 This is the X-ray diffraction analysis diagram of VC prepared in Example 2;
[0023] Figure 3 This is a scanning electron microscope image of the Bi2MoO6 / VC / CC photoelectric catalyst prepared in Example 2 at 5 um;
[0024] Figure 4 This is the oxygen evolution performance diagram of Bi2MoO6 / VC / CC prepared in Example 2 in a solution with a pH of 9.5. DETAILED DESCRIPTION
[0025] The specific contents of the present invention are further explained in detail below in conjunction with embodiments.
[0026] The reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art. The experimental methods in the following examples where specific experimental conditions are not specified are usually carried out under conventional experimental conditions. Unless otherwise specified, the reagents and raw materials used in the present invention can be obtained commercially.
[0027] In the following embodiments, the CC substrate is cleaned by placing the substrate in a beaker and ultrasonically cleaning it with water and alcohol for 20 minutes.
[0028] Example 1
[0029] Step 1, sodium molybdate dihydrate and bismuth nitrate pentahydrate powders are prepared in a mass ratio of 1:1, ground with a mortar for 5 minutes until the mixture is uniformly mixed to obtain a mixed powder, placed in a white magnetic boat, placed in a tube furnace, and heated to 500°C at a rate of 5°C / min under the protection of an inert atmosphere of Ar, and kept warm for 4 hours. After the product is cooled, it is taken out and transferred to a centrifuge tube, centrifuged at 8000r / min for 15 minutes, rinsed alternately with deionized water and anhydrous ethanol three times, and after removing the supernatant, a precipitate is obtained. The product is placed in a vacuum drying oven at 80°C and dried for 8 hours, taken out and ground with a mortar for 40 minutes to obtain a Bi2MoO6 precursor;
[0030] Step 2: ammonium metavanadate, dicyandiamide, and urea are mixed in a mass ratio of 1:0.5:1, ground in a mortar for 5 minutes until the mixture is uniformly mixed to obtain a mixed powder, placed in a white magnetic boat, placed in a tubular furnace, and heated to 800°C at a rate of 5°C / min under the protection of an inert atmosphere of Ar, and kept warm for 4 hours. After the product is cooled, it is taken out and ground in a mortar for 40 minutes to obtain VC powder;
[0031] Step 3: Take 0.3 g of the Bi2MoO6 powder prepared in step 1 and the VC powder prepared in step 2 and place them in the same beaker, add 30 mL of deionized water, stir for 10 min at a stirring rate of 500 r / min, then add 0.005 g of polyvinyl alcohol (PVA), continue stirring for 5 min until evenly dispersed, and obtain precursor solution B, and transfer solution B to a crucible;
[0032] Step 4. Set the working temperature of the muffle furnace to 140°C. When the temperature inside the muffle furnace rises to the set temperature, place the crucible in the muffle furnace and keep it warm for 15 minutes. Then, take it out with crucible tongs, turn off the equipment, immerse the cleaned CC substrate in the solution for 10 minutes, then take it out. Take out the CC substrate, put it in a vacuum drying oven at 80°C and dry it for 8 hours. Then, the required Bi2MoO6 / VC / CC photoelectric catalyst can be obtained.
[0033] The photoelectrocatalytic effect of Bi2MoO6 / VC / CC was tested using chi660e equipment. The specific test process includes cutting the composite photoelectrocatalyst into 1*1.5cm size, placing it in a sodium tetraborate solution with a pH of 9.5, and conducting a photoelectrocatalytic oxygen evolution test.
[0034] Embodiment 2:
[0035] Step 1, sodium molybdate dihydrate and bismuth nitrate pentahydrate powders are prepared in a mass ratio of 1:2, ground with a mortar for 5 minutes until the mixture is uniformly mixed to obtain a mixed powder, placed in a white magnetic boat, placed in a tube furnace, and heated to 600°C at a rate of 10°C / min under the protection of an inert atmosphere of Ar, and kept warm for 3 hours. After the product is cooled, it is taken out and transferred to a centrifuge tube, centrifuged at 8000r / min for 5 minutes, rinsed alternately with deionized water and anhydrous ethanol three times, and after removing the supernatant, a precipitate is obtained. The product is placed in a vacuum drying oven at 80°C for 12 hours, taken out and ground with a mortar for 80 minutes, which is a Bi2MoO6 precursor;
[0036] Step 2: ammonium metavanadate, dicyandiamide, and urea are mixed in a mass ratio of 1:2:3, ground in a mortar for 5 minutes until the mixture is uniformly mixed to obtain a mixed powder, placed in a white magnetic boat, placed in a tube furnace, and heated to 900°C at a rate of 10°C / min under the protection of an inert atmosphere of Ar, and kept warm for 3 hours. After the product is cooled, it is taken out and ground in a mortar for 80 minutes to obtain VC powder;
[0037] Step 3: Take 0.45g of the Bi2MoO6 powder prepared in step 1 and the VC powder prepared in step 2 and place them in the same beaker, add 40mL of deionized water, stir for 5min at a stirring rate of 700r / min, then add 0.01g of polyvinyl alcohol (PVA), continue stirring for 10min until uniformly dispersed, and obtain precursor solution B, and transfer solution B to a crucible;
[0038] Step 4: Set the working temperature of the muffle furnace to 160°C. When the temperature inside the muffle furnace rises to the set temperature, place the crucible in the muffle furnace and keep it warm for 10 minutes. Then, take it out with crucible tongs, turn off the equipment, immerse the cleaned CC substrate in the solution for 5 minutes, then take it out. Take out the CC substrate, put it in a vacuum drying oven at 80°C and dry it for 12 hours. Then, the required Bi2MoO6 / VC / CC photoelectric catalyst can be obtained.
[0039] The photoelectrocatalytic effect of Bi2MoO6 / VC / CC was tested using chi660e equipment. The specific test process includes cutting the composite photoelectrocatalyst into 1*1.5cm size, placing it in a sodium tetraborate solution with a pH of 9.5, and conducting a photoelectrocatalytic oxygen evolution test.
[0040] Figure 1 This is the X-ray diffraction analysis diagram of Bi2MoO6 prepared in Example 2, where the horizontal axis is the 2θ angle and the vertical axis is the diffraction peak intensity. In addition, Bi2MoO6 can accurately correspond to the Bi2MoO6 PDF#76-2388 card, indicating that Bi2MoO6 powder was successfully prepared;
[0041] Figure 2 This is the X-ray diffraction analysis diagram of VC prepared in Example 2, where the horizontal axis is the 2θ angle and the vertical axis is the diffraction peak intensity. At the same time, VC can accurately correspond to the VC PDF#73-0476 card, indicating that VC powder is successfully prepared;
[0042] Figure 3 This is a scanning electron microscope image of the Bi2MoO6 / VC / CC photoelectric catalyst prepared in Example 2 at 5 μm. It can be seen from the figure that Bi2MoO 6 / VC powder was successfully deposited on the CC substrate;
[0043] Figure 4 This is the oxygen evolution performance diagram of Bi2MoO6 / VC / CC prepared in Example 2 in a solution with a pH of 9.5. The composite photoelectric catalyst exhibits a current of 4.2 mA / cm at 1.23 V. 2 overpotential.
[0044] Embodiment 3:
[0045] Step 1, sodium molybdate dihydrate and bismuth nitrate pentahydrate powders are prepared in a mass ratio of 1:3, ground with a mortar for 5 minutes until the mixture is uniformly mixed to obtain a mixed powder, placed in a white magnetic boat, placed in a tube furnace, and heated to 700°C at a rate of 20°C / min under the protection of an inert atmosphere of Ar, and kept warm for 2 hours. After the product is cooled, it is taken out and transferred to a centrifuge tube, centrifuged at 12000r / min for 5 minutes, rinsed alternately with deionized water and anhydrous ethanol three times, and after removing the supernatant, a precipitate is obtained. The product is placed in a vacuum drying oven at 80°C for 16 hours, taken out and ground with a mortar for 120 minutes, which is a Bi2MoO6 precursor;
[0046] Step 2: ammonium metavanadate, dicyandiamide, and urea are mixed in a mass ratio of 1:4:5, ground in a mortar for 5 minutes until the mixture is uniformly mixed to obtain a mixed powder, placed in a white magnetic boat, placed in a tube furnace, and heated to 1000°C at a rate of 20°C / min under the protection of an inert atmosphere of Ar, and kept warm for 2 hours. After the product is cooled, it is taken out and ground in a mortar for 120 minutes to obtain VC powder;
[0047] Step 3: Take 0.6 g of the Bi2MoO6 powder prepared in step 1 and the VC powder prepared in step 2 and place them in the same beaker, add 50 mL of deionized water, stir for 8 min at a stirring rate of 600 r / min, then add 0.02 g of polyvinyl alcohol (PVA), continue stirring for 8 min until the mixture is evenly dispersed, and obtain a precursor solution B, which is then transferred to a crucible;
[0048] Step 4: Set the working temperature of the muffle furnace to 180°C. When the temperature inside the muffle furnace rises to the set temperature, place the crucible in the muffle furnace and keep it warm for 5 minutes. Then, take it out with crucible tongs, turn off the equipment, immerse the cleaned CC substrate in the solution for 1 minute, then take it out. Take out the CC substrate, put it in a vacuum drying oven at 80°C and dry it for 16 hours. Then, the required Bi2MoO6 / VC / CC photoelectric catalyst can be obtained.
[0049] The photoelectrocatalytic effect of Bi2MoO6 / VC / CC was tested using chi660e equipment. The specific test process includes cutting the composite photoelectrocatalyst into 1*1.5cm size, placing it in a sodium tetraborate solution with a pH of 9.5, and conducting a photoelectrocatalytic oxygen evolution test.
[0050] Embodiment 4:
[0051] Step 1, sodium molybdate dihydrate and bismuth nitrate pentahydrate powders are prepared in a mass ratio of 1:1.5, ground with a mortar for 5 minutes until the mixture is uniformly mixed to obtain a mixed powder, placed in a white magnetic boat, placed in a tube furnace, and heated to 700°C at a rate of 15°C / min under the protection of an inert atmosphere of Ar, and kept warm for 2 hours. After the product is cooled, it is taken out and transferred to a centrifuge tube, centrifuged at 12000r / min for 5 minutes, rinsed alternately with deionized water and anhydrous ethanol three times, and after removing the supernatant, a precipitate is obtained. The product is placed in a vacuum drying oven at 80°C and dried for 16 hours, taken out and ground with a mortar for 120 minutes to obtain a Bi2MoO6 precursor;
[0052] Step 2: ammonium metavanadate, dicyandiamide, and urea are mixed in a mass ratio of 1:0.5:5, ground in a mortar for 5 minutes until the mixture is uniformly mixed to obtain a mixed powder, placed in a white magnetic boat, placed in a tube furnace, and heated to 1000°C at a rate of 20°C / min under the protection of an inert atmosphere of Ar, and kept warm for 2 hours. After the product is cooled, it is taken out and ground in a mortar for 120 minutes to obtain VC powder;
[0053] Step 3: Take 0.6 g of the Bi2MoO6 powder prepared in step 1 and the VC powder prepared in step 2 and place them in the same beaker, add 50 mL of deionized water, stir for 8 min at a stirring rate of 600 r / min, then add 0.02 g of polyvinyl alcohol (PVA), continue stirring for 8 min until the mixture is evenly dispersed, and obtain a precursor solution B, which is then transferred to a crucible;
[0054] Step 4: Set the working temperature of the muffle furnace to 180°C. When the temperature inside the muffle furnace rises to the set temperature, place the crucible in the muffle furnace and keep it warm for 5 minutes. Then, take it out with crucible tongs, turn off the equipment, immerse the cleaned CC substrate in the solution for 1 minute, then take it out. Take out the CC substrate, put it in a vacuum drying oven at 80°C and dry it for 16 hours. Then, the required Bi2MoO6 / VC / CC photoelectric catalyst can be obtained.
[0055] The photoelectrocatalytic effect of Bi2MoO6 / VC / CC was tested using chi660e equipment. The specific test process includes cutting the composite photoelectrocatalyst into 1*1.5cm size, placing it in a sodium tetraborate solution with a pH of 9.5, and conducting a photoelectrocatalytic oxygen evolution test.
[0056] Embodiment 5:
[0057] Step 1, sodium molybdate dihydrate and bismuth nitrate pentahydrate powders are prepared in a mass ratio of 1:2.5, ground with a mortar for 5 minutes until the mixture is uniformly mixed to obtain a mixed powder, placed in a white magnetic boat, placed in a tube furnace, and heated to 700°C at a rate of 20°C / min under the protection of an inert atmosphere of Ar, and kept warm for 2 hours. After the product is cooled, it is taken out and transferred to a centrifuge tube, centrifuged at 12000r / min for 5 minutes, rinsed alternately with deionized water and anhydrous ethanol three times, and after removing the supernatant, a precipitate is obtained. The product is placed in a vacuum drying oven at 80°C for 16 hours, taken out and ground with a mortar for 120 minutes, which is a Bi2MoO6 precursor;
[0058] Step 2: ammonium metavanadate, dicyandiamide, and urea are mixed in a mass ratio of 1:4:1, ground in a mortar for 5 minutes until the mixture is uniformly mixed to obtain a mixed powder, placed in a white magnetic boat, placed in a tube furnace, and heated to 1000°C at a rate of 20°C / min under the protection of an inert atmosphere of Ar, and kept warm for 2 hours. After the product is cooled, it is taken out and ground in a mortar for 120 minutes to obtain VC powder;
[0059] Step 3: Take 0.5 g of the Bi2MoO6 powder prepared in step 1 and the VC powder prepared in step 2 and place them in the same beaker, add 50 mL of deionized water, stir for 8 min at a stirring rate of 600 r / min, then add 0.02 g of polyvinyl alcohol (PVA), continue stirring for 8 min until the mixture is evenly dispersed, and obtain a precursor solution B, which is then transferred to a crucible;
[0060] Step 4: Set the working temperature of the muffle furnace to 180°C. When the temperature inside the muffle furnace rises to the set temperature, place the crucible in the muffle furnace and keep it warm for 5 minutes. Then, take it out with crucible tongs, turn off the equipment, immerse the cleaned CC substrate in the solution for 1 minute, then take it out. Take out the CC substrate, put it in a vacuum drying oven at 80°C and dry it for 16 hours. Then, the required Bi2MoO6 / VC / CC photoelectric catalyst can be obtained.
[0061] The photoelectrocatalytic effect of Bi2MoO6 / VC / CC was tested using chi660e equipment. The specific test process includes cutting the composite photoelectrocatalyst into 1*1.5cm size, placing it in a sodium tetraborate solution with a pH of 9.5, and conducting a photoelectrocatalytic oxygen evolution test.
[0062] It should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it; without departing from the concept of the present invention, the deduction or replacement made by those skilled in the art shall fall within the protection scope of the present invention.
Claims
1. A method for preparing a Bi2MoO6 / VC / CC composite photoelectrocatalyst, characterized in that: The following steps are involved: Step 1: Sodium molybdate dihydrate and bismuth nitrate pentahydrate powders are prepared in a mass ratio of 1: (1-3), mixed evenly, and placed in a white magnetic boat, which is then placed in a tube furnace. Under the protection of an inert atmosphere of Ar, the temperature is raised from room temperature to 500-700°C at a rate of 5-20°C / min, and the temperature is kept for 2-4 hours. After the product is cooled, it is taken out for centrifugal washing, dried, and then ground to obtain a Bi2MoO6 precursor; Step 2: ammonium metavanadate, dicyandiamide and urea are mixed in a mass ratio of 1:(0.5-4):(1-5), placed in a white magnetic boat, put into a tube furnace, and heated from room temperature to 800-1000°C at a rate of 5-20°C / min under the protection of an inert atmosphere of Ar, and kept warm for 2-4 hours. After the product is cooled, it is taken out and ground to obtain VC powder; Step 3: Take 0.3-0.6 g of Bi2MoO6 powder prepared in step 1 and VC powder prepared in step 2 and place them in the same beaker, add 30-50 mL of deionized water, stir until uniformly dispersed, then add 0.005-0.02 g of polyvinyl alcohol, continue stirring until uniformly dispersed, obtain a precursor solution and transfer it to a crucible; Step 4: Set the working temperature of the muffle furnace to 140-180°C. When the temperature inside the muffle furnace rises to the set temperature, place the crucible containing the precursor solution in the muffle furnace and keep it warm for 5-15 minutes. Then, take it out with crucible tongs, immerse the cleaned CC substrate in the solution for 1-10 minutes, take out the CC substrate, and obtain the desired Bi2MoO6 / VC / CC photoelectric catalyst after drying.
2. The method for preparing the Bi2MoO6 / VC / CC composite photoelectrocatalyst according to claim 1, characterized in that: The grinding described in step 1 and step 2 is grinding with a mortar for 40 to 120 minutes.
3. The method for preparing the Bi2MoO6 / VC / CC composite photoelectrocatalyst according to claim 1, characterized in that: The centrifugal washing described in step 1 is to transfer the product to a centrifuge tube, separate the solid after centrifugation at 8000-12000 r / min for 5-15 minutes, and rinse it alternately with deionized water and anhydrous ethanol for 3-5 times.
4. The method for preparing the Bi2MoO6 / VC / CC composite photoelectrocatalyst according to claim 1, characterized in that: The drying described in step 1 and step 4 is to place the product in a vacuum drying oven at 80° C. and dry it for 8 to 16 hours.
5. The method for preparing the Bi2MoO6 / VC / CC composite photoelectrocatalyst according to claim 1, characterized in that: The stirring time described in step 3 is 5 to 10 minutes, and the stirring rate is 500 to 700 r / min.
6. The method for preparing the Bi2MoO6 / VC / CC composite photoelectrocatalyst according to claim 1, characterized in that: The CC substrate cleaning method described in step 4 is to place the substrate in a beaker and use water and alcohol to alternately ultrasonically clean it for 20 minutes.
7. A Bi2MoO6 / VC / CC composite photoelectric catalyst prepared by the method as described in any one of claims 1 to 6.
8. Use of the Bi2MoO6 / VC / CC composite photoelectrocatalyst as claimed in claim 7 as a photoanode in photocatalytic electrolysis of water.
Citation Information
Patent Citations
Bi2MoO6 / CuO photoelectrode film, preparation method thereof and application of Bi2MoO6 / CuO photoelectrode film in photoelectrochemical water decomposition
CN114737217A
Efficient BiVO4 / Mo2C composite photoelectric catalytic material as well as preparation method and application thereof
CN117987876A
Efficient Ni17W3 / WC electro-catalytic material as well as preparation method and application thereof
CN118086969A